Development of Local Culture-Based Image Media to Improve Student Learning Outcomes on the Material of Arithmetic Operations of Multiplication of Natural Numbers: Pengembangan Media Gambar Berbasis Kebudayaan Lokal Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Operasi Hitung Perkalian Bilangan Asli - Putri Tria Sundari; Sihabudin Sihabudin; Mansur Mansur (Institute of Advanced Knowledge and Science, 2024)
The aim of this research is to develop Image Media learning media to calculate the multiplication of natural numbers for class II students at SDN Tejamari, Baros District. This research uses the type of research and development (R&D) from S. Thiagarajan's development model, which has 4 stages of development, namely defining, designing, developing and disseminating. The media developed is validated by material experts and media experts before conducting initial field trials on students. Data was collected using questionnaires from media experts, material experts, class II teacher questionnaires, student questionnaires, interview observations and documentation. Data resulting from research were analyzed using quantitative and qualitative analysis techniques. Based on the validation results, material experts got a score of 46 with a percentage of 83% with the criteria